Is there a prognostic role of K-ras point mutations in the serum of patients with advanced non-small cell lung cancer? - Camps, Carlos; Sirera, Rafael; Bremnes, Roy; Blasco, Ana; Sancho, Eva; Bayo, Pilar; Safont, Maria Jose; Sánchez, José Javier; Tarón, Miquel; Rosell, Rafael (Lung cancer (Amsterdam, Netherlands), 2005)
The purpose of this study was to investigate the prognostic significance of K-ras mutations in circulating DNA in advanced non-small lung cancer (NSCLC) patients. Serum samples were assessed prior to platinum-based chemotherapy start in 67 patients with advanced NSCLC (stage IIIB or IV), treated between April 1999 and June 2002. Patients were not previously treated with chemotherapy. K-ras oncogene mutations at codon 12 were analyzed by genomic amplification and direct sequencing of the patient's DNA present in serum. Pre-treatment serum was available in all 67 patients. Twenty patients (30%) demonstrated K-ras mutations while 47 patients (70%) had wild-type K-ras. Among K-ras mutations, the amino acid glycine was substituted by cystein in 90% and valine in 10%. When patients were grouped according to K-ras genotype, there was no significant difference for any of the baseline patient characteristics. There was a tendency towards a higher response rate for patients with K-ras mutations versus wild-type K-ras in serum, however not statistically significant ( p = 0.37). Median progression-free survival was 7.3 months versus 5.5 months in patients with mutations and with wild-type K-ras, respectively ( p = 0.23). For median overall survival time, the mutation group was comparable to the wild-type K-ras group with 12.5 and 11.4 months, respectively ( p = 0.28). In conclusion, there were no significant differences between the patients with K-ras mutations and those with wild-type genotype with respect to baseline patient characteristics, response rates, progression-free survival, or overall survival.